O brakteatach trochę inaczej - Rosen-Przeworska, Janina (1906–1991) (Zakład Narodowy im. Ossolińskich, 1980)
P. 203-216 : ill. ; 25 cm
Bibliography p. 215-216
Keywords: 4th-6th c. -- Europe; late Roman-Migration period coins; brakteats; brakteats -- genesis; Celtic coins; Celtic coins -- iconography

Brakteaty z Wapna (pow. Wągrówiec) na tle porównawczym - Żak, Jan (1923–1990) (Polskie Towarzystwo Prehistoryczne, 1951)
ill. ; 29 cm
Keywords: golden bracteates; Scandinavian imports -- Poland; Wapno, Wągrowiec district (Poland)

O znaczeniu archeologicznego kontekstu znalezisk także w badaniach historyków w związku z nowszymi hipotezami na temat atrybucji tzw. brakteatów tamańskich - Kollinger, Karol (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2018)
The author presents the state of research and a critical review of existing hypotheses, as well as a historical summary of issues related to the dating and attribution of the so-called Taman bracteates. It is an excellent example of the importance of the archaeological context, without which any interpretation is doomed to be based on more or less probable hypotheses. The author does not believe it possible today to attribute these „bracteates” to Vsevolod II Olgovič or to Mstislav Vladimirovič, at least for now; he is also critical of any consideration in this context of the seal attributed to Michael Oleg Svyatoslavič, as this artifact may very well be a modern fake. He shares the doubts of some researchers regarding the authenticity of newer finds of single „bracteates”. He favors distinguishing three separate „bracteate” types: the first, bearing the so-called sign of the Rurikids, should be viewed as being of 11th c. date (it resembles the sign on coins of Svyatopolk I), whereas the other two, both with representations of the archangel Michael, would be of 12th and 13th c. date respectively. The source base today is insufficient in the author’s opinion to determine who issued these so-called Taman bracteates and when. The situation may change with new finds coming from archaeological contexts
ill.; 24 cm
Keywords: Taman Peninsula; Tmutarakan’; Taman bracteates; finds context; coins; modern fakes; dating; sign of the Rurikids

Śląskie pojemniki na brakteaty na tle porównawczym - Wachowski, Krzysztof (1943– ) (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2002)
P. 345-354 : ill. ; 25 cm
Bibliography p. 353-354
German summary
Keywords: early Middle Ages -- Poland; early medieval silver coins; bracteates; early medieval containers for coins; Silesia (Poland)

Skandynawski skarb złotych przedmiotów z przełomu starożytności i średniowiecza z miejscowości Wapno, woj. pilskie - Kara, Michał (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 1994)
The article presents an analysis of a hoard of golden objects discovered in Wapno in the last century. The analysis was carried out with regard to the contents of the hoard, its character, chronology, and origin. It was determined that the objects (among others Nordic golden brakteats of C type according to O. Montelius) were part of 3 separate Scandinavian deposits (treasures) of ritualistic character, re-buried at the end of the 5th c. - the beginning of the 6th c. AD in gravemounds of Pomeranian culture from the Hallstatt D period. A hypothesis was proposed that the golden treasures most probably belonged to a small group of Scandinavians who in the area of Wapno took up exploitation of local deposits of rock salt as well as initial distribution of this article, considered lucrative and popular in the period of Migration of Nations
ill. ; 29 cm
Keywords: hoard; coin; Poland; Scandinavia; Migration period -- Poland; hoards of golden objects; finds of Scandinavian provenance -- Poland; Scandinavian golden brakteats; Wapno (Poland)